Hubungan Dukungan Sosial dengan Tingkat adaptasi Santri di Pondok Pesantren Nurul Islam Daerah Al- Kautsar Karang Cempaka Bluto - Riza Bela Hanani; Mafruhah; Anis Tri Yuliana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adaptation or self-adjustment is a process that involves mental and behavioral aspects of a person in facing a new environment in order to achieve a balance between self-demands and the environment. This process involves efforts to overcome stress, frustration, and internal conflict. Social support is the presence and involvement of others who are able to provide feelings of security, comfort, and appreciation for students through attention, assistance, and positive relationships including social support in terms of emotional, instrumental, and effective aspects that play an important role in helping students adapt and prevent feelings of loneliness and improve students' psychological well-being. This study aims to determine the relationship between social support and the level of self-adjustment of students at the Nurul Islam Islamic Boarding School in the Al-Kautsar Karang Cempaka Bluto area. The quantitative correlation method was used to determine the interaction between variables X and Y. Participants were selected using saturated sampling, consisting of 27 female students. Data analysis in this study used the Pearson Product Moment correlation technique to determine the relationship between social support and the level of student adaptation. The results of the study showed a significance value of 0.124 (p > 0.005), indicating no significant relationship between social support and student adaptation. This indicates that changes in variable X were not followed by consistent changes in variable Y in this study sample.